Common Credit Units, and Projected Unit Cost of Credit Methods - Maghfirani, Nazla Aqira (Indonesian Operations Research Association (IORA), 2021)
Pension funds are funds collected by the company as the rights of a retiree from the company. Pension funds are usually in the form of money that can be taken every month or taken all at once when someone enters retirement, and the amount of pension funds must be calculated carefully. This paper aims to be able to perform actuarial calculations on traditional credit units, and perform calculations on several methods of calculating the projected salary scale. The calculation results obtained total actuarial liabilities, and total normal costs for pension fund program participants, so that it can be used as an illustration for pension plan participants to estimate how much pension benefits will be received at retirement.